2021
DOI: 10.2147/nss.s329038
|View full text |Cite
|
Sign up to set email alerts
|

The Associations of Trajectory of Sleep Duration and Inflammation with Hypertension: A Longitudinal Study in China

Abstract: Background: Existing evidence suggested that sleep duration may be involved in hypertension; however, the conclusions were still controversial. This study aimed to examine the association of longitudinal trajectory of sleep duration with hypertension and to explore the role of the inflammation in such associations. Methods: A total of 3178 subjects over 30 years of age without hypertension were enrolled in 2004, and they were followed until 2009. Self-reported sleep duration was recorded, and inflammation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“… 35 It is worth emphasizing that changes in sleep duration, especially a decrease in sleep duration, may be associated with higher risks of negative health outcomes such as hypertension. 36 , 37 The latest study found new evidence and suggested that sleep irregularity, particularly sleep duration irregularity, was associated with an increased risk of several measures of subclinical atherosclerosis and that sleep regularity may be a modifiable target for reducing atherosclerosis risk. 38 Therefore, sufficient and regular sleep duration were both vital factors for maintaining good sleep health.…”
Section: Discussionmentioning
confidence: 99%
“… 35 It is worth emphasizing that changes in sleep duration, especially a decrease in sleep duration, may be associated with higher risks of negative health outcomes such as hypertension. 36 , 37 The latest study found new evidence and suggested that sleep irregularity, particularly sleep duration irregularity, was associated with an increased risk of several measures of subclinical atherosclerosis and that sleep regularity may be a modifiable target for reducing atherosclerosis risk. 38 Therefore, sufficient and regular sleep duration were both vital factors for maintaining good sleep health.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen studies evaluated the effect of long sleep duration (> 8 hours) on the risk of HTN incidence [ 21 , 23 26 , 29 32 , 34 , 35 , 37 39 ]. In the pooled analysis, we did not discern any significant correlation between long sleep duration and risk of developing HTN (HR: 1.01, 95% CI: 1–1.03).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have linked long sleep duration to higher systemic inflammatory responses, where the inflammatory cytokines including C-reactive protein (CRP) and interleukin-6 (IL-6) were upregulated in people with longer sleep duration [35][36][37]. In patients with chronic NCD, the inflammation could accelerate the progressive condition of NCD, thus increasing mortality risk.…”
Section: Discussionmentioning
confidence: 99%